KOMUNIKASI STRATEGIS BAWASLU DALAM MENYEBARLUASKAN INFORMASI HUKUM MELALUI JDIH MENJELANG PEMILU DAN PEMILIHAN SERENTAK 2024 DI JAWA BARAT - Nur Hayati, Neni (Jurnal Keadilan Pemilu, 2022)
The complexities of election and simultaneous election in 2024 have brought difcult challenge. This research aims at revealing strategic communication of Election Monitoring Institute (Bawaslu) in disseminating legal information and legal products through JDIH to general public. This research employs qualitative method with case study approach. This study proves that JDIH of West Java Election Monitoring Institute (Bawaslu) has actively socialized and educated public with various programs to inform legal product it issued. However, the medium used is very limited as the disseminations were conned to conventional media such as internet. This method is insufcient, as in the context of West Java, internet has been massively used and public has been fed with overwhelming information. In addition, in the post truth era, democracy can potentially turn into threat, as the combination of wide use of internet and open and unrestricted public sphere could potentially lead to the massive circulation of hoax, misinformation and disinformation. Based on this reality, considering use of social media platform as means of dissemination is inevitable. Moreover, strategic communication can be taken by dening goals and objects, determining social media platform and evaluating existing strategy, media monitoring and observation.